2008
DOI: 10.4039/n08-035
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent powder marking reduces condition but not survivorship in adult mountain pine beetles

Abstract: We investigated the impact of different fluorescent marking powders on both survivorship and daily body condition, measured as mass/volume ratio, using adult mountain pine beetles, Dendroctonus ponderosae Hopkins (Coleoptera: Curculionidae: Scolytinae), in a laboratory study. Initial condition of the marked beetle groups did not differ from that of an unmarked group. However, beetles in better initial condition survived longer, thus validating our condition index. The condition but not the survivorship of moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Marking experiments on mountain pine beetles ( Dentroctonus ponderosae , Coleoptera: Cucurlionidae), however, showed that fluorescent dyes did not reduce the viability of the beetles but they influenced their physical condition. The authors presumed, therefore, that fluorescent powders might affect optimal dispersal behaviour (Reid and Reid ).…”
Section: Discussionmentioning
confidence: 99%
“…Marking experiments on mountain pine beetles ( Dentroctonus ponderosae , Coleoptera: Cucurlionidae), however, showed that fluorescent dyes did not reduce the viability of the beetles but they influenced their physical condition. The authors presumed, therefore, that fluorescent powders might affect optimal dispersal behaviour (Reid and Reid ).…”
Section: Discussionmentioning
confidence: 99%
“…Mark-recapture involves the collection or rearing of the target insect followed by the release of marked individuals at a specific location. Bark beetles have been marked externally with paint or coloured powder or by elytra engraving (Jactel 1991;Duelli et al 1997;Barclay et al 1998;Reid and Reid 2008;Doležal et al 2016) prior to release in forest stands. Application of powder to the outside of beetle-infested tree bolts allows for passive marking of beetles as they emerge from the bolt.…”
Section: Dendroctonus Ponderosaementioning
confidence: 99%
“…However, caution is warranted when applying this method to different organisms as chemical application may have distinct effects . Indeed, Reid and Reid have found that fluorescent marking can induce a faster mass loss in Dendroctonus ponderosae (Coleoptera: Curculionidae) compared to unmarked individuals. Our results demonstrate that fluorescent marking does not affect the basic biology, including survivorship, of H. longicornis , indicating its adequacy for tracking ticks.…”
Section: Discussionmentioning
confidence: 99%